Estrogen Receptor α Mediates Doxorubicin Sensitivity in Breast Cancer Cells by Regulating E-Cadherin - Wan, Xiaoqing; Hou, Jiaxin; Liu, Shurong; Zhang, Yanli; Li, Wenqing; Zhang, Yanru; Ding, Yi (Frontiers in Cell and Developmental Biology, 2021)
Anthracyclines resistance is commonly seen in patients with estrogen receptor α (ERα) positive breast cancer. Epithelial-mesenchymal transition (EMT), which is characterized with the loss of epithelial cell polarity, cell adhesion and acquisition of new invasive property, is considered as one of the mechanisms of chemotherapy-induced drug resistance. In order to identify factors that associated with doxorubicin resistance, we performed in vitro and in vivo experiments using human and mouse breast cancer cell lines with different ERα status. Cell survival experiments revealed that ERα-positive cells (MCF-7 and MCF-7/ADR cell lines), were less sensitive to doxorubicin than ERα-negative (MDA-MB-231, MDA-MB-468) cells, and mouse mammary carcinoma cells (4T-1). The expression of E-cadherin reduced in low-invasive ERα-positive MCF-7 cells after treatment with doxorubicin, indicating epithelial mesenchymal transition. In contrast, the expression of E-cadherin was upregulated in high-invasive ERα-negative cells, showing mesenchymal-epithelial transition (MET). Moreover, it was found that the growth inhibition of 4T-1 cells by doxorubicin was positively correlated with the expression of E-cadherin. In a mouse breast cancer xenograft model, E-cadherin was overexpressed in the primary tumor tissues of the doxorubicin-treated mice. In ERα-positive MCF-7 cells, doxorubicin treatment upregulated the expression of EMT-related transcription factors Snail and Twist, that regulate the expression of E-cadherin. Following overexpression of ERα in ERα-negative cells (MDA-MB-231 and MDA-MB-468), doxorubicin enhanced the upregulation of Snail and Twist, decreased expression of E-cadherin, and decreased the sensitivity of cells to doxorubicin. In contrast, inhibition of ERα activity increased the sensitivity to doxorubicin in ERα-positive MCF-7 cells. These data suggest that the regulation of Snail and / or Twist varies depends on different ERα status. Therefore, doxorubicin combined with anti-estrogen receptor α therapy could improve the treatment efficacy of doxorubicin in ERα-positive breast cancer.